Analisis Fungsi Peribahsa Jepang Yang Mengandung Unsur Binatang - Suhervina Sinta wati; Hendri Zalman (Omiyage : Jurnal Bahasa dan Pembelajaran Bahasa Jepang, 2021)
Japanesse proverb(kotowaza) is an expression which is figurately expressed by someone to another one as an insinuation, advice, life experience, and a game. There are a lot of Japanesse proverb use the parable / comparison, one of the parable/ comparison object used in it is animals. Japenesse proverb is one of the subjects that hard to learned and umderstood, especially for the foreign learner ( example indonesian ). This research discuss the analysis of Japeness proverb which contain the word animals taken from happy lilac websitae . The purpose of this research is to know about what kind of animal that contain in kotozawa and its function. The data in this research is the kotozawa that contain of animal words which taken from happy lilac website and the methodein this research is qualitative descriptive. The data collection technique in this research is the library technique. Based on the resaerch result 23 from 210 kotozawa that contain of animal words, 7 of them contain the offensive function (kougekiteki kotowaza), 6 kotowaza contain empiric function (keikenteki kotowaza), 10 kotowaza dictative function (kyoukunteki kotowaza) and none of kotowaza that contain the game (kyoukunteki kotowaza)